The Effectiveness of Public Sector Governance at the Ministry of Health of the Republic of Indonesia - Pratama, Andhika Yudha; Ermawati, Wita Juwita; Suprayitno, Gendut (CV. Publikasi Indonesia, 2024)
The rapid development of the times always demands changes in every sector, including in the scope of government. In running the government system, good public sector governance is needed, where its implementation is further developed through bureaucratic reform, which refers to Presidential Regulation Number 81 of 2010 concerning the Grand Design of Bureaucratic Reform 2010-2025. As one of the government agencies, the implementation of bureaucratic reform is carried out by the Ministry of Health of the Republic of Indonesia, one of which is realized through strengthening performance accountability, which refers to Presidential Regulation Number 29 of 2014 concerning the Performance Accountability System of Government Agencies. The results of the evaluation of the 2015-2022 Government Agency Performance Accountability assessment are always at the predicate of